Compacted Laser‐Induced Graphene with Bamboo‐Like Carbon Nanotubes for Transformable Capacitive Energy Storage Electrodes. Issue 7 (7th December 2021) - Hyeong, Seok‐Ki; Park, Mina; Kim, Seung‐Il; Park, Seoungwoong; Choi, Kwang‐Hun; Im, Min Ji; Kim, Nam Dong; Kim, Tae‐Wook; Lee, Sang Hyun; Park, Ji‐Won; Bae, Sukang; Lee, Jae‐Hyun; et al.
Abstract: Laser‐induced graphene (LIG) has drawn attention for energy storage devices owing to its fascinating material properties as well as for its use in the effective production of porous structures. However, the low packing density of LIG, which is caused by macroscopic voids owing to rapid degassing during the instantaneous photothermal process, limits the improvement of device performance. Herein, the fabrication of compacted LIG composite is introduced, wherein, the unused voids are filled with bamboo‐like carbon nanotubes (BCNTs). The BCNTs grown directly in the voids of LIG through chemical vapor deposition (CVD) method using Cu seeds as catalysts improve the electrical conductivity, chemical activity, and mechanical flexibility, while enhancing the spatial efficiency of the porous structure. Consequently, the fabricated composite film (denoted as BCNT:LIG/Cu) delivers an energy density of 1.87 μWh cm −2, which is ≈10 times higher than that of the LIG‐based supercapacitor (0.19 μWh cm −2 ). Moreover, the BCNT:LIG/Cu film with a shape engineering pattern is assembled into a solid‐state supercapacitor using a gel electrolyte (PVA‐KOH), showing excellent electrochemical and mechanical stabilities under complex deformations. The proposed LIG‐based densification strategy opens up opportunities for the development of energy devices for portable power supply in practical applications. Abstract : A 3D porous composite is fabricated using laser‐induced graphene (LIG) to use the large amount of void space via the direct growth of bamboo‐like carbon nanotubes on LIG. The composite exhibits improved capacitive and mechanical performance owing to its hierarchical structure. Also, the composite shows a transformable supercapacitor characteristic even under complex deformation owing to excellent electrochemical and mechanical stabilities.